2016
DOI: 10.1111/imb.12222
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of clathrin‐mediated endocytosis and two Sid‐1‐like transmembrane proteins in double‐stranded RNA uptake in the Colorado potato beetle midgut

Abstract: RNA interference (RNAi) is a powerful tool in entomology and shows promise as a crop protection strategy, but variability in its efficiency across different insect species limits its applicability. For oral uptake of the double-stranded RNA (dsRNA), the RNAi trigger, two different mechanisms are known: systemic RNA interference deficient-1 (Sid-1) transmembrane channel-mediated uptake and clathrin-mediated endocytosis. So far, a wide range of experiments has been conducted, confirming the involvement of one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
165
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(184 citation statements)
references
References 41 publications
3
165
1
1
Order By: Relevance
“…Apart from degradation in the digestive system, other research has shown the importance of functional uptake mechanisms for dsRNA. In insects, the primary mode of cellular uptake of dsRNA appears to be scavenger receptor-mediated endocytosis (Cappelle et al, 2016;Ivashuta et al, 2015;Li et al, 2015;Saleh et al, 2006;Ulvila et al, 2006;Wynant et al, 2014;Xiao et al, 2015;Yoon et al, 2016). Interestingly, also in adults of S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from degradation in the digestive system, other research has shown the importance of functional uptake mechanisms for dsRNA. In insects, the primary mode of cellular uptake of dsRNA appears to be scavenger receptor-mediated endocytosis (Cappelle et al, 2016;Ivashuta et al, 2015;Li et al, 2015;Saleh et al, 2006;Ulvila et al, 2006;Wynant et al, 2014;Xiao et al, 2015;Yoon et al, 2016). Interestingly, also in adults of S.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by the ability to quickly develop resistance to a wide range of chemical pesticides, urging the need to develop alternative management strategies (Zhu et al, 2011). Several studies have shown that CPB is able to take up dsRNA from the gut lumen and subsequently induce a potent systemic RNAi response, suggesting that RNAi could be a feasible novel control method for this insect pest (Cappelle et al, 2016;Zhu et al, 2011). Until now no high nuclease activity has been demonstrated in the gut juice of CPB.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, environmental RNAi needs cooperation between Sid-1 and Sid-2 proteins. The Sid-1 genes seem to be present in most insect species, but so far no Sid-2 genes have been found in insect species whose genomes have been sequenced (e.g., Tomoyasu et al, 2008; Xu and Han, 2008; Zha et al, 2011; Cappelle et al, 2016). A phylogenetic analysis suggested that Sid-1 like genes in Tribolium may not be orthologous to Sid-1 , but rather to the C. elegans Tag-130 gene which is not associated in systemic RNAi in nematodes (Tomoyasu et al, 2008).…”
Section: What Matters For Rnai Efficiency?mentioning
confidence: 99%
“…However, the importance of the endocytic pathway has been shown in the oriental fruit fly 88 and both SID-like proteins and endocytosis are important in the dietary uptake of sRNA in in the Colorado potato beetle. 89 These data suggest that endocytosis may be a common mechanism for sRNA uptake by the cells of the digestive tract.…”
Section: Do Srnas Cross the Digestive Tract Barrier?mentioning
confidence: 90%
“…However, as pointed out in the recent study by Capelle et al, both pathways have rarely been examined in a given insect species making comprehensive comparison difficult. 89 In the tick and the desert locust, the scavenger receptor has been implicated in endocytosis-mediated spread, 138,139 which may indicate that this receptor is commonly used for this mechanism; however, other receptors yet to be discovered may also be employed for sRNA recognition. In addition, cells of different tissues within an organism can have different potential for uptake.…”
Section: Is There Cellular Uptake Of Srnas?mentioning
confidence: 99%